Peningkatan Keterampilan Membatik Para Santriwati Pondok Pesantren Khoirul Huda 1 Surabaya dengan Membuat Berbagai Desain Motif Batik - Novianarenti, Eky; Sa'diyah, Aminatus; Santoso, Emie; Dwijati, Daisy; Sriwijayasih, Imaniah (Politeknik Piksi Ganesha Indonesia, 2025)
The low level of traditional art skills and economic independence among female students (santriwati) at Pondok Pesantren Khoirul Huda 1 Surabaya is a major issue. This community service program aims to develop batik-making skills through various motif designs, enhance entrepreneurial spirit, and preserve local culture. The method used is a comprehensive training approach through lectures, demonstrations, and hands-on practice. Activities include delivering basic batik materials, training in designing motifs, canting techniques, coloring, and product finishing. The program successfully increased the santriwati’s knowledge and skills in batik-making, produced high-value products, and opened opportunities for creative entrepreneurship. The long-term impact includes the development of a pesantren-based batik center and a positive contribution to community economic empowerment through the preservation of traditional arts integrated with Islamic values.